Battery Demonstration for Household Electrical Energy Education among Indonesian Elementary Pupils - Muhammad Fajar Wahyu Pratama; Dian Efytra Yuliana; Ertika Fitri Lisnanti (Penerbit Goodwood, 2026)
Purpose: This community service study examined whether a simple battery demonstration could support Indonesian elementary pupils’ understanding of household electrical energy sources and energy transformation. Research Methodology: The activity was conducted in August in Kuala Lumpur, Malaysia, with Indonesian elementary-age children. Fourteen pupils joined the learning session, while quantitative analysis used 14 complete pre-test and post-test score pairs available in the score sheet. The demonstration kit consisted of a battery, connecting wires, a light-emitting diode, a small propeller, and reused plastic bottles as the tool frame. Learning was implemented through a brief explanation, guided demonstration, hands-on practice, discussion, and a five-item test. Results: The mean score increased from 3.286 (SD = 0.825) before the activity to 4.357 (SD = 0.929) after the activity. A paired-sample t-test showed a significant improvement, t(13) = 4.020, p = 0.001, with a large within-participant effect size (Cohen’s dz = 1.074). Conclusions: The demonstration helped pupils observe that a battery can function as an electrical energy source and that electrical energy may be transformed into light and motion. Limitations: The study was limited by the small sample, short intervention, five-item instrument, and absence of a control group. Contributions: The article offers a low-cost, replicable model for elementary science outreach in Indonesian overseas learning communities.